2019
DOI: 10.5812/ijcm.87246
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Pap Smear Screening Behavior Among Rural Women in Tabriz, Iran: An Application of Health Belief Model

Abstract: Background: In order to increase the acceptance level of the cervical cancer screening behavior among women, understanding the associated factors of the behavior is necessary. Objectives: The aim of this study was to evaluate the cognitive determinants of Pap smear screening (PSS) behaviors among rural women in Tabriz, Iran. Methods: In this cross sectional study, multistage random sampling was employed to recruit 220 rural women in Tabriz, Iran. A valid and reliable health behavior model (HBM)-based instrumen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
(39 reference statements)
0
8
0
Order By: Relevance
“…In Iran, several studies have reported low participation rate in the test. For instance, this rate in study of Babazade et al [12] was reported 27.1% and in study of Farzane et al [13] was reported 50%. In the case study province (Guilan) this rate was 0.31% and in Shaft county was 17.59%.…”
Section: Introductionmentioning
confidence: 86%
“…In Iran, several studies have reported low participation rate in the test. For instance, this rate in study of Babazade et al [12] was reported 27.1% and in study of Farzane et al [13] was reported 50%. In the case study province (Guilan) this rate was 0.31% and in Shaft county was 17.59%.…”
Section: Introductionmentioning
confidence: 86%
“…As a result, it's critical to investigate the direct risk factors for cervical cancer that are prevalent in various populations of women, as well as the cognitive, emotional, and environmental elements that may play a role in women's willingness to engage in preventive screening programs. So, Health Belief Model (HBM) has been considered one of the most representative ones due to its effectiveness in explaining change and maintaining healthy behavior (Babazadeh et al, 2019& Musa et al, 2017 The Health Belief Model was created in 1950 by a social psychologist working for the United States Public Health Service to explain why so many people fail to participate in disease prevention and detection programs. The model was then modified to investigate people's reactions to symptoms and behaviors in response to confirmed sickness, including adherence to medical regimens.…”
Section: Introductionmentioning
confidence: 99%
“…In line with our study, the perceived benefits were a predictor of cervical cancer screening behavior in both univariate and multivariate models. In the final model, which produced more accurate results, perceived benefits were the best predictor of women receiving a screening test (Babazadeh et al, 2019). Perceived barriers and perceived severity were found to be predictive of cervical cancer screening successful test in Hope et al study (Hope, Moss, Redman, & Sherman, 2017).…”
Section: Discussionmentioning
confidence: 92%